The importance of territory in defining social enterprises from urban peripheries (Gestão & Regionalidade, 2024)
Assuming that there is a lack of consensus in defining social enterprises and given the acknowledged heterogeneity of these ventures, this work aims to understand to what extent the characteristics of socio enterprises adhere to the context of low-income urban areas. By running a multiple case study with the companies Enjoy Alimentação Orgânica and Jaubra, it was possible to identify that, although the characteristics of social enterprises can provide entrepreneurs in low-income areas with greater legitimacy before different audiences, these characteristics are poorly adherent to the context of popular territories. This article contributes to the debate about bringing up the need for consensual definitions, which may foster future models that apply to different realities. In a managerial context, it is proposed that, if acknowledged as social enterprises, these businesses may have their legitimacy reinforced and, consequently, their outcomes and the local ecosystem in low-income areas will be fostered.
Keywords: social entrepreneurship; urban peripheries; social enterprises